SYSTEM OF AUTOMATIOZATION OF TECHNOLOGY PROCESS CONTROL OF AEROSOL NANOCATALYSYS WITH VIBRATING BED - Riazantsev, O. I.; Kardashuk, V. S. (Radio Electronics, Computer Science, Control, 2010)
The author proposes an automatic control system for the process of aerosol nanocatalysis with vibrating bed to be used in environmentally appropriate systems of organic-chlorine synthesis products neutralization using modern programtechnical means. Functional and structural organization of the system, its software support and results of software model experimental investigation are described.